AI-Enabled Marketing Transformation in the Indian Pharmaceutical Sector - M. Venkatesulu (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This research paper explores the impact of Artificial Intelligence (AI) on the Indian pharmaceutical industry and how it has revolutionized marketing practices. This study examines the use of AI technology like predictive analytics, machine learning, chatbots, customer relationship management systems, and customised digital marketing for improving efficiency, customer interactions, and decision-making in pharmaceutical marketing. The paper emphasizes how AI tools are increasingly being used by pharma firms to gain insights into customer behavior, increase sales efficiency, target physicians more effectively, and enhance patient engagement. It also discusses the pros and cons of using AI, such as privacy issues, ethics, technical and infrastructure requirements, and changing the way employees work. The research methodology used is an Analytical and Exploratory approach with Secondary data (Based on the Industrial Reports, Journals and Case Studies of the Indian Pharmaceuticals market). The results reveal that AI-driven marketing transformation has a proven impact on boosting operational efficiency, market responsiveness, and competitive advantage, which fosters the sustainable development and digital transformation of the pharmaceutical industry in India.